Percepção dos pais quanto aos impactos da pandemia do covid-19 no processo de aprendizagem infantil - Brito, Maria Milena Sousa de; Santos, Pâmela Pontes dos; Delgado, Isabelle Cahino (Distúrbios da Comunicação, 2023)
Introduction: In 2020, the pandemic of COVID-19 changed the world scenario when the WHO declared a Public Health Emergency. With the temporary changes resulting from the pandemic and as a consequence of social isolation, several sectors underwent temporary adaptations and readjustments. To reduce the impact, classes have been resumed through Emergency Remote Education (ERE). With these abrupt changes, the family’s role in the children’s learning process became more and more primordial. Objective: To analyze the learning of children in kindergarten and elementary school in the private network, from the perspective of parents regarding remote school practices during social isolation. Method: Cross-sectional, exploratory, quantitative-qualitative study was carried out using a questionnaire containing objective and discursive questions in an online format. The research was approved by the Ethics and Research with Human Beings Committee, under protocol number 4.473.160. Results: Parents state that they did not notice any difficulty in the children’s learning and that it was not necessary to make purchases of electronic devices during the period. However, there was curricular flexibility. The participants pointed out that most schools did not offer training to use digital resources. And, they also mention that there was a change in the mood and behavior of the children. Conclusion: In theory, Emergency Remote Learning was necessary for the continuity of the learning process, but adversities were encountered during the course because schools and families were not prepared for this reality.